Comparative Assessment of Weed Control Methods and Their Impact on Rice Yield in Eastern Terai, Nepal - Rai, Sabina (Agronomy Journal of Nepal, 2025)
Rice (Oryza sativa L.) is the most important cereal crop in Nepal, but its production is greatly challenged by weed infestation. Weed infestation is one of the major constraints to rice productivity in South Asia, including Nepal. This study evaluated the comparative performance of chemical and mechanical weed control methods in rice cultivation in Kamal area of Jhapa district, Eastern Terai, Nepal. A field-based socio-economic survey was conducted during the 2018 rice growing season using simple random sampling. A total of 37 rice-growing households were selected, and data were collected through household surveys, interviews, and focus group discussions. Data were analyzed using descriptive statistics including frequency and percentage analysis. Results showed that chemical weed control was the dominant method adopted by farmers, mainly due to labor scarcity and ease of application. Major weeds identified included Cyperus rotundus, Fimbristylis miliacea, Monochoria vaginalis, and Echinochloa colona. The average cost of cultivation was lower under chemical weed control (Rs 1968 kattha-1) compared to mechanical weed control (Rs 2218 kattha-1). However, average yield and gross return were similar under both methods (1.4 Qt kattha-1and Rs 3150 kattha-1, respectively). The benefit-cost ratio was higher for chemical weed control (1.6) compared to mechanical control (1.4). The findings indicate that chemical weed control currently provides higher economic efficiency under local farming conditions. However, long-term sustainability, environmental safety, and integrated weed management approaches should be emphasized. This study provides baseline information for extension programs and policy interventions aimed at improving rice productivity and profitability in Eastern Nepal.